Pharmacists' perception on medication errors in intensive care unit - Mohamed Ariffin, Suzilawati; Mohamed Ludin, Salizar; Aung, Khin Thandar (Lincoln University College, Asia Pacific Higher Learning Sdn Bhd., 2020)
Introduction:Medication error is a global issue. A medication error is one of the medical errors that can result from mild to severe complications which may violate patient safety. A holistic approach is important to prevent medication error includes contributed factor, reporting system and training for staffs. Objective:This research sought to determine the pharmacists' perception of medication errors in the intensive care unit. Methodology:This descriptive cross-sectional study involved 132 pharmacists from two hospitals in state of Pahang, Malaysia. A self-administrated questionnaire was used to collect the data. Statistical analysis of the data was carried out using SPSS and association between variables was analyzed using one way ANOVA and multiple regression tests. Result: The findings show that interruptions (x=̅3.40) as the commonest cause of dispensing errors perceived by pharmacists, followed by pharmacists fatigue at any cause (x ̅= 3.20) and pharmacist overwork (x=̅3.17). Besides, 51% of participants practice dispensing less than 10 hours per week on average. 54% and 55% of participants believe the increase of risk of error in dispensing and actual errors become more common in pharmacy practice, respectively. The results also showed that only level of education has a significant association with possible factors in dispensing medication among the pharmacists at the hospital (P=0.000). Besides, multiple regressions showed no significant relationship between both dependent variables. Conclusion: Most of the pharmacist perceived those possible factors associated with dispensing error. This study suggests that pharmacists should be well informed regarding dispensing error in order to be more alert. Besides, future study should be more specific on pharmacists who assigned to the in-patient department.